PENINGKATAN MUTU KARYA TULIS DOSEN FIS DENGAN MENGGUNAKAN REFERENCE MANAGER SOFTWARE MENDELEY (Harmony: Jurnal Pembelajaran IPS dan PKN, 2018)
The rapid development of technology has had an impact on various sectors, including in the research sector, activities of managing references can use technology in the form of reference management software. The purpose of this community service is: (1) to examine the obstacles faced by Unnes FIS lecturers in quoting scientific papers; (2) reviewing the implementation of citation in scientific papers that have been carried out by Unnes FIS lecturers; (3) provide training on the use of reference manager software for Unnes FIS lecturers. The method of implementing community service activities is based on two approaches namely textual and contextual. The procedures for community service activities include: (1) exploratory: problem identification; (2) topical: submission of material about compilation of quotations that are in accordance with Mendeley's reference manager program; (3) monitoring and evaluation: assistance and program evaluation. The results of these community service activities are: (1) module products in the form of Mendeley usage manuals; (2) service products in the form of training of use reference manager software Mendeley. Perkembangan teknologi yang sangat pesat menyebabkan dampak pada berbagai lini kehidupan, termasuk teknologi dalam bidang penelitian, kegiatan mengelola referensi dapat menggunakan teknologi berupa perangkat lunak manajer referensi (reference management). Tujuan dari pengabdian ini adalah: (1) mengkaji apa saja kendala yang dihadapi oleh dosen FIS Unnes dalam pengutipan karya tulis ilmiah; (2) mengkaji pelaksanaan pengutipan dalam karya tulis ilmiah yang selama ini diakukan oleh dosen FIS Unnes; (3) memberikan pelatihan penggunaan reference manager software untuk dosen FIS Unnes. Metode pelaksanaan kegiatan PPM didasarkan pada dua pendekatan yaitu tekstual dan kontekstual. Prosedur kegiatan PPM meliputi: (10 eksploratory: identifikasi masalah; (2) topical: penyampaian materi tentang penyusunan pengutipan yang sesuai standar menggunakan program reference manager Mendeley; (3) monitoring and evaluation: pendampingan dan evaluasi program. Hasil dari kegiatan PPM ini adalah: (1) produk modul berupa buku pedoman penggunaan Mendeley; (2) produk jasa berupa layanan pelatihan penggunaan program reference manager Mendeley.